Chapter 1.1 Pro Kind Ein Modellversuch Früher Hilfen - Brand, Tilman (Edition Sozial, 2013)
In the following we will first locate the early help in the area child protection. Then the conceptual Background of the model project shown per child. So prevention can be effective and efficient in addition to a well-founded concept design ensure that the concept is as intended and implemented with high quality in practice. The implementation experiences, that were made as part of the model project Pro Kind, are the central theme of this book. To the structuring The following explanations are based on Results of prevention, organizational and diffusion research Core components to ensure the implementation quality as a basic framework presents.